Keabsahan Perkawinan dalam Perspektif Adat Towani Tolotang : Studi di Kabupaten Sidrap Provinsi Sulawesi Selatan - Rukdah Tufatul Ilmi (International Forum of Researchers and Lecturers, 2025)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife whose aim is to form a happy and eternal family (household) based on the belief in the Almighty God. Law 1/1974 refers to the validity of a marriage held by Indonesian citizens based on the laws of their respective religions and beliefs. The aim of this thesis is to analyze the Towani Tolotang Traditional Marriage process in relation to Hindu Religious Marriages and analyze the validity of Towani Tolotang Traditional Marriages Based on Marriage Law in Indonesia. It becomes a problem when a community of Towani Tolotang believers are